Preliminary study on community's perception of seagrass restoration on Pari Island, Seribu Islands Regency. Issue 1 (January 2022) - Sjafrie, N D M; Triyono,; Zulpikar, F; Rahmawati, S; Hernawan, U E
Abstract: Pari Island is one of the islands located in the Seribu Islands Regency. Seagrasses on this island are scattered almost around the island. However, development on this island is overgrowing, so there is a decrease in the seagrass area. This study aims to determine the community's perception of the possibility of seagrass restoration on the island. Data collection was conducted in May 2021 through a questionnaire. Respondents were local people of Pari Island. The number of respondents was 104 people consisting of fishers, housewifes, government employees, tourism actors, students, and entrepreneurs. The results showed that, in general, people in Pari Island know the existence of seagrass (99%), understand the functions and benefits of seagrass (100%), and use the biota that lives in the seagrass ecosystem for their lives, as household food needs. Almost all respondents agreed with the seagrass restoration in Pari Island (96%) and voluntarily participated in restoration activities (91%). A total of 90% of respondents agree that there is a regulation on protecting seagrass meadow and say that restoration efforts must involve local communities, Non-Government organizations (NGOs), Research Institutes or Universities, and the Government. Our finding shows that the local community in Pari Island has a deep concern for seagrass restoration.